Sources and Variations in Social Support and Risk for Elder Mistreatment in a US Chinese Population. (12th August 2019) - Zheng, Shenglin; Li, Mengting; Kong, Dexia; Dong, XinQi
Abstract : OBJECTIVES: Research has examined the relationships between positive social support (PSS) and elder mistreatment (EM) but less is known regarding the negative aspect of social support (NSS), especially among minority groups in the United States. This study aimed to investigate the relationships between PSS/NSS from different sources and EM among US Chinese older adults. Design: Population‐based cross‐sectional study. Setting: Greater Chicago, IL, area. PARTICIPANTS: A representative sample of Chinese older adults aged 60 years or older (N = 3157) from the Population Study of ChINese Elderly in Chicago in 2011 to 2013. Measurements: We applied a 10‐item widely used instrument to assess EM. PSS and NSS from spouse/family members/friends were measured by a 12‐item scale. Multivariate logistic regression analyses were conducted to examine the relationships. RESULTS: After adjusting for confounders, higher levels of overall PSS from all three sources, including spouse, family members, and friends (odds ratio [OR] = 0.88 [95% confidence interval CI = 0.85‐0.91]), were associated with lower risk of EM. But participants with a higher level of overall NSS from all three sources (OR = 1.51 [95% CI = 1.41‐1.61]) were more likely to experience EM. The results on the relationships between PSS from spouse (OR = 0.70 [95% CI = 0.64‐0.76]), PSS from family members (OR = 0.73 [95% CI = 0.68‐0.79]), and EM were similar to overall PSS. But PSS from friends had a nonsignificant association with EM. Greater levels of NSS from spouse (OR = 1.84 [95% CI = 1.64‐2.07]), family members (OR = 2.36 [95% CI = 2.03‐2.75]), and friends (OR = 1.69 [95% CI = 1.32‐2.17]) were associated with increased risks of EM. CONCLUSION: Higher levels of SS were not always associated with lower risks of EM among US Chinese older adults. NSS might have counter effects. Future qualitative or longitudinal research needs to explore detailed cultural explanations and casual relationships between SS and EM. J Am Geriatr Soc 67:S499–S505, 2019.